MyPlantDIY (Malaysian plant diagnose it yourself) app - Badaluddin, Noor Afiza; Yusoff, Nornasuha; Sajili, Mohammad Hailmi; Kadir, Jugah (Centre for Global Open Access Learning, Immersive Technology & Quality Assurance, Universiti Sains Islam Malaysia, 2017)
The databases of plant disease in Malaysia are already being published in the printed (academic book) and digital form (internet blog). Hence, MyPlantDIY app is innovated by converting these database into easy, fast, up to date and user friendly form. MyPlantDIY app provides the images, the description and the suggested treatments for the particular disease. Besides, MyPlantDIY consists interactive module that can be used as discussion platform and data collection. Thus, MyPlantDIY app provides real pictures of local plant disease and the users can real time compare and diagnose their plant problem rapidly.